Association between neighborhood disadvantage and children's oral health outcomes in urban families in the Chicago area - Lee, Helen H.; Dziak, John J.; Avenetti, David M.; Berbaum, Michael L.; Edomwande, Yuwa; Kliebhan, Margaret; Zhang, Tong; Licona-Martinez, Karla; Martin, Molly A. (Frontiers in Public Health, 2023)
Purpose The prevalence of childhood caries in urban Chicago, compared with national and state data, indicates that neighborhood context influences oral health. Our objective was to delineate the influence of a child's neighborhood on oral health outcomes that are predictive of caries (toothbrushing frequency and plaque levels). Methods Our study population represents urban, Medicaid-enrolled families in the metropolitan Chicago area. Data were obtained from a cohort of participants (child–parent dyads) who participated in the Coordinated Oral Health Promotion (CO-OP) trial at 12 months of study participation (N = 362). Oral health outcomes included toothbrushing frequency and plaque levels. Participants' neighborhood resource levels were measured by the Area Deprivation Index (ADI). Linear and logistic regression models were used to measure the influence of ADI on plaque scores and toothbrushing frequency, respectively. Results Data from 362 child–parent dyads were analyzed. The mean child age was 33.6 months (SD 6.8). The majority of children were reported to brush at least twice daily (n = 228, 63%), but the mean plaque score was 1.9 (SD 0.7), classified as “poor.” In covariate-adjusted analyses, ADI was not associated with brushing frequency (0.94, 95% CI 0.84–1.06). ADI was associated with plaque scores (0.05, 95% CI 0.01–0.09, p value = 0.007). Conclusions Findings support the hypothesis that neighborhood-level factors influence children's plaque levels. Because excessive plaque places a child at high risk for cavities, we recommend the inclusion of neighborhood context in interventions and policies to reduce children's oral health disparities. Existing programs and clinics that serve disadvantaged communities are well-positioned to support caregivers of young children in maintaining recommended oral health behaviors.